Investigating Translation Errors in Recount Texts: A Study of Midwifery Students’ use of Machine Translation - Sulistiyaningsih, Eka Fanti; Wafa, Zaenul; Susilowati, Endang (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Translation is process transfer information or idea from Source Language (SL) to Target Language (TL) without change the meaning of the words or sentences. The research aimed to investigate translation errors of using machine translation in students’ midwifery programs in writing a recount text. The research design of this research was a qualitative research design. Content analysis is used by the researcher to investigate the translation errors of machine translation used in students’ midwifery recount texts. The data was collected purposively from 21 students of the midwifery program. The data sources of this research were students’ recount texts translated using machine translation. The types of data that were collected by the researcher were words, phrases, and sentences. The researcher used documentation and a questionnaire as the instruments of this research to collect the data. The result of the research showed that the most dominant categories of translation errors were orthographic errors (35,3%), consisting of Orthographic Errors Punctuation (24,6%) and Orthographic Errors Capitalization (10,7%). Then, the second category was Semantic errors (29,2%). The next categories were Morphological Errors Verb (21,5%) and Syntactic errors (12,1%) consist of Syntactic errors Conjunction (7,6%), Syntactic errors Prepositions (3%), and Syntactic errors Article (1,5%). The last category found by the researcher was Lexical errors, Missing words (1,5%). Further research is needed to find the way how to decrease the error translation in Machine Translation (MT)